The Perceptions of English Education Students on AI-Powered Tools for Developing Writing Skills - Milatul Auliya Dewi; Tria Moulina; Rizky Septian Rahayu; Yessi Nurul Rahmi; Lystiana Nurhayat Hakim (Journal of Applied Linguistics (ALTICS), 2025)
This study explores English education students' perceptions of AI-powered tools in developing writing skills through a quantitative survey administered to students across various Indonesian universities. The research employs a structured questionnaire to gather insights on the effectiveness, usability, and impact of tools such as Grammarly, Quillbot, and ChatGPT on students' writing practices. Key findings indicate a general positive perception among students, highlighting the tools' role in enhancing writing quality and accessibility. The study also examines variations in perception based on students' levels of familiarity with these tools, providing a nuanced understanding of their practical benefits and limitations. This investigation contributes to the growing discourse on the integration of AI in educational contexts and offers valuable insights for future research and practical applications in English language teaching. Keywords: Artificial intelligence, writing tools, EFL, Indonesian universities, student perception